Case of Erythroderma Skin Disorder Caused by Drug Eruption - Idris, Irma Suryani; Purnamasari, A. Bida; Suryani, A. Irma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Erythrodema or also called exfoliative dermatitis is an inflammatory skin disease with erythema and fine scales that affect almost the entire surface of the skin. Histopathological examination will vary and sometimes be non-specific, depending on the triggering disease. Generally there is hyperkeratosis with focal parakeratosis, mild acanthosis and chronic inflammatory cell infiltration. The author would like to report a case of erythroderma in a 62 year old woman who was hospitalized for 8 days. The diagnosis is made based on the history, clinical picture and histopathological examination. The results of the case report found that skin tissue preparations showed that the epidermis had regenerated. The superficial dermis appears as mild perivascular lymphocytic accompanied by 1-2 eosinophils.